Mechanical Control of the Floating Type Aquatic Weed Salvinia Molesta (African Payal) - Sankaranarayanan M R (Department of Agricultural Engineering, College of Horticulture, 1981)
Salvlnia molesta, locally known as ’African Payal‘ is a noxious floating type aquatic weed of common occurance, particularly in the State of Kerala in India* The infestation is the heaviest in the Kuttanadu region and in the Kole lands of Trichur District of the State, where alone more than 50,000 hectares of inland water surface is under the grip of this weed. In the present project, the possibilities of mechanical control of the Salvinia weed were investigated* The study concentrated on the development and evaluation of a prototype Salvinia harvesting Machine which utilised a novel design concept of fluidising the mass by means of a centrifugal* ejector pump combination* The machine consisted of two 5 H.P portable pumpsets as the prime mover and an ejector system mounted on a floating platform. The machine pump out the weed-water mixture into a floating filtering unit at zero lift from which the water was drained by gravity, the material was automatically loaded into a country boat. The results of tests conducted indicated that the 10 H.Pmachine was capable of pumping the Salvinia weed at an average rate of 16 T/hr at zero lift conditions. The proportion of the weed pumped was of the order of 15 % by weight of the secondary flow when pump¬ing water alone. The special features of this equipment were that it could utilise conventional Irrigation punpsets as the prime mover and that it did not allow the weed materials to be drawn into and clog the primary pump. The machine was also capable of being operated as a self propelled unit.